Preparation method of ferric hydroxide loaded cellulose fluorescent adsorption material with Cr < 6 + > adsorbability and detectability and taking steel slag as iron source
By preparing iron hydroxide-loaded cellulose fluorescent adsorption materials, the problems of low steel slag utilization and complex heavy metal ion treatment were solved, efficient heavy metal ion adsorption and visual detection were achieved, and resource utilization and environmental friendliness were achieved.
Patent Information
- Application Number
- CN202510863124.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-09-23
AI Technical Summary
In the existing technology, the utilization rate of steel slag is low, and the existing adsorption materials have problems such as complex process, high cost, poor adsorption effect and possible secondary pollution when treating heavy metal ions. In addition, colorless and odorless heavy metal ions are difficult to detect through instruments.
Steel slag is used as the iron source to prepare iron hydroxide-loaded cellulose fluorescent adsorption material. The adsorption and visual detection of heavy metal ions are achieved through the sol-gel method combined with the fluorescence detection of carbon quantum dots.
It realizes the resource utilization of steel slag, provides efficient heavy metal ion adsorption and visual detection, reduces costs, avoids secondary pollution, and improves the adsorption performance of the adsorption material.
Smart Images

Figure CN120679500A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of preparation of composite adsorption materials, and relates to a method for preparing a ferric hydroxide-loaded cellulose fluorescent adsorption material using steel slag as an iron source, which is simultaneously used for heavy metal ion adsorption and fluorescence detection, and a ferric hydroxide-loaded cellulose fluorescent adsorption material using steel slag as an iron source. Background technology:
[0002] With the continuous development of industrial technology, global water pollution is becoming increasingly serious. Heavy metal ion pollution is one of the typical wastewater pollutants. Excessive heavy metal levels in the human body can cause serious harm to the body. Common heavy metal ions include iron, lead, cadmium, arsenic, mercury, chromium, copper, manganese, etc. At present, industrial wastewater treatment methods have problems such as complex processes and high costs. In addition, the removal of heavy metal ions in wastewater can only rely on instrument detection, especially some colorless and odorless heavy metal ions, which to some extent limits the application of these methods in wastewater treatment.
[0003] In view of the above problems, it is particularly necessary to find a low-cost, simple process and visual wastewater purification method. As a commonly used wastewater purification method, adsorption method has the advantages of wide application range, low cost, simple process and good purification effect. It usually uses the characteristics of the adsorption material and the active functional groups on the surface to react with heavy metal ions through ion exchange, chelation, chemical precipitation and electrostatic attraction, so that they are loaded on the surface of the adsorption material to achieve the purpose of wastewater purification. At the same time, carbon quantum dots have the advantages of strong fluorescence emission, small size and good stability. They can react chemically with heavy metal ions to produce fluorescence quenching effect and are widely used in the field of heavy metal ion detection. Combining an adsorbent with high adsorption capacity with carbon quantum dots with fluorescence detection performance can significantly improve the adsorption performance of the adsorbent.
[0004] As a by-product of the steel industry, steel slag has a high annual output and a complex chemical composition. It is mainly composed of mineral phases such as silicate phase and iron-containing phase. After ball milling pretreatment, the obtained steel slag powder has a porous structure with a rough surface, which gives it good adsorption capacity. Non-patent document 1 reports on the study of wastewater treatment using biocarbon composite materials prepared from steel slag and Hami melon peel. This technology has the advantages of low cost and simple process. However, the adsorption material prepared using this technology has a long reaction time and poor adsorption effect. And due to the complex chemical composition of steel slag, it is easy to cause secondary pollution problems.
[0005] In recent years, prior art reports have described processes for leaching valuable elements from steel slag. Application number CN201410049610, invention title: Method for producing high-purity light calcium carbonate from steel slag. The steel slag is first ground into powder to expose the free calcium oxide in the slag on the surface. A wet leaching process is then employed, using 0.5% acetic acid to extract the calcium oxide from the slag. After filtering and clarification, carbon dioxide gas is introduced for carbonization. The product is then dehydrated, washed, dried, cooled, crushed, and screened to produce high-purity light calcium carbonate. While this process is simple to operate, it can only extract the free calcium oxide from the slag and cannot effectively leach elements such as calcium and iron from the mineral phase of the slag. This is detrimental to the practical utilization of steel slag.
[0006] Cellulose, a biomass polymer widely found in nature, offers advantages such as low cost, good biocompatibility, and ease of modification, making it an ideal material for preparing gels. Non-Patent Document 2 reports on the purification of heavy metal ion wastewater using carboxymethyl cellulose hydrogels. While this process effectively removes pollutants, it also suffers from a low adsorption capacity, an inability to effectively utilize the active functional groups on the carboxymethyl cellulose surface, and an inability to effectively observe the hydrogel's adsorption effect on heavy metal ions.
[0007] This shows that extracting valuable elements from steel slag and reusing them for secondary use has great development potential. Based on existing research and technology, combining steel slag products with biomass materials to prepare highly adsorbable, pollution-free, and visual composite adsorption materials can effectively meet the practical application needs of industrial development.
[0008] Existing literature:
[0009] Non-patented Document 1: Sun L, Wu J, Wang J, et al. Fabricating hydroxyapatite functionalized biochar composite using steel slag and Hami melon peel for Pb(II) and Cd(II)removal[J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2023, 666: 131310.
[0010] Non-patentedDocument 2: Velempini T, Pillay K, Mbianda XY, et al. Carboxymethylcellulose thiol-imprinted polymers: Synthesis, characterization and selective Hg(II)adsorption[J]. Journal of Environmental Sciences, 2019, 79: 280-296. Summary of the invention:
[0011] The present invention provides a method for preparing a novel iron hydroxide-loaded cellulose fluorescent adsorption material, which has the characteristics of metal ion adsorption and fluorescence detection. It helps promote the resource utilization of steel slag and solve the problem of heavy metal water pollution.
[0012] The present invention provides a Cr 6+ The preparation method of a cellulose fluorescent adsorption material loaded with iron hydroxide using steel slag as an iron source and having good adsorption and detection properties comprises the following steps:
[0013] (1) Dissolve steel slag powder in a container A filled with an acid solution of a certain concentration to obtain a uniformly mixed steel slag mixture, which is heated, stirred, and centrifuged to obtain leachate A and leach slag A.
[0014] (2) The pH of the obtained leachate A is adjusted with an alkaline solution of a certain concentration, and after stirring for a certain period of time, a reddish-brown mixed solution is obtained. After centrifugation, washing, and drying, a reddish-brown substance B is obtained, which is ferric hydroxide.
[0015] (3) At least one selected from lignin, cellulose and citric acid as a carbon source and at least one selected from dopamine, o-phenylenediamine and ethylenediamine as a nitrogen source are placed in a sealed container B for reaction, and a carbon quantum dot solution C is obtained after dialysis.
[0016] (4) The adsorption material is prepared by a sol-gel method, wherein a reddish-brown substance B, a polymer having an amino group, at least one selected from glutaraldehyde and epichlorohydrin as a cross-linking agent, and a cellulose-based substance having hydroxyl groups and carboxyl groups are uniformly mixed in water to obtain a sol D, which is washed after ultrasonication and reaction, and then immersed in a carbon quantum dot solution C; after washing and freeze-drying, the iron hydroxide-loaded cellulose fluorescent adsorption material with steel slag as the iron source is obtained.
[0017] In step (1), in order to effectively extract the iron ions in the steel slag, the steel slag used can be selected as far as possible with a higher iron content. The present invention has no special requirements on the particle size of the steel slag. According to the actual experimental requirements, the steel slag particles can be pre-treated by ball milling, for example, grinding to an average particle size D of the steel slag powder. 50 10-20μm.
[0018] Furthermore, in step (1), the concentration of the steel slag powder is 70-170 g / L, preferably 100-150 g / L; the acid concentration used is 5 wt%-40 wt%, preferably 10 wt%-30 wt%; there is no special restriction on container A, as long as the experiment can be carried out smoothly; the stirring speed is 200-500 rpm, preferably 300-500 rpm; the heating temperature is 25-70 ° C, preferably 40-60 ° C; the stirring time is 1-6 h, more preferably 2-4 h.
[0019] Furthermore, in step (2), the concentration of the alkali solution is 10wt%-30wt%, preferably 15wt%-25wt%; the mechanical stirring speed is 200-500rpm, preferably 300-500rpm; the centrifugal speed is 5000-6000rpm, preferably 5500-6000rpm; the washing number is 2-4 times, preferably 2-3 times; and the drying time is 12-48h, preferably 18-48h.
[0020] Furthermore, in step (3), the carbon source can be selected from biomass polymer materials such as citric acid, lignin, or cellulose, and the sealed container B can be a commonly used high-pressure reactor. There is no specific requirement for the reactor volume. The molecular weight cut-off of the dialysis bag is generally 3500-8000, which can be adjusted according to experimental requirements. The dialysis time is generally 1-2 days, which can be adjusted according to the dialysis situation.
[0021] Furthermore, in step (4), in order to prepare the fluorescent adsorption material, the amount of the added reddish-brown substance B is about 0.1-0.4 g, the selected concentration of the polymer with amino group is 2%-4%, the added amount is 3-6 mL, the added amount of carboxymethyl cellulose is 0.5-1.0 g, and the added amount of the cross-linking agent is 2-4 mL; in order to eliminate the bubbles inside the cellulose hydrogel, the sol D can be subjected to ultrasonic defoaming treatment, the ultrasonic time is 40-60 min, and the better choice is 50-60 min; the reaction temperature is 50-70 ° C, and the better choice is 55-65 ° C; the reaction time is 2-4 h, and the better choice is 3-4 h; the immersion time in the carbon quantum dot solution C is 24-48 h, and the better choice is 36-48 h, and the number of washings is 2-3 times.
[0022] In addition, in order to further increase the active sites on the surface of the adsorption material, a reagent having an amino active functional group, such as dopamine, o-phenylenediamine, ethylenediamine, etc., is added in step (3) in an amount of 1.0-1.5 g. The hydrothermal reaction temperature is 150-200°C and the reaction time is 3-5 hours.
[0023] In addition, in order to avoid the agglomeration of the reddish-brown substance B in the carboxymethyl cellulose sol, the reddish-brown substance B needs to be ultrasonically treated so as to be uniformly dispersed in the sol D.
[0024] The beneficial effects of the present invention are:
[0025] By loading ferric hydroxide prepared from steel slag as the iron source onto carboxymethyl cellulose hydrogel, the shortcomings of ferric hydroxide agglomeration and a lack of active functional groups were effectively addressed. Furthermore, by preparing a fluorescent cellulose adsorption material loaded with ferric hydroxide, it was possible to achieve wastewater purification and visual adsorption of heavy metal ions.
[0026] In addition, by using steel slag as a source of iron hydroxide, the resource utilization of steel slag is realized, which can help solve the environmental pollution problem caused by large-scale stacking of steel slag, achieve the goal of "treating waste with waste", and open up new ways for the value-added utilization of steel slag. Description of the drawings:
[0027] The present invention will be further described below with reference to the accompanying drawings and specific embodiments:
[0028] Figure 1 is the X-ray diffraction pattern of the reddish-brown substance B obtained in Reference Example 1;
[0029] Figure 2 is a Fourier transform infrared spectrum of the carbon quantum dot solution C prepared in Reference Example 1;
[0030] Figure 3 The Cr was determined in Example 1. 6+ Standard working curve of concentration;
[0031] Figure 4 This is the XPS spectrum of the iron hydroxide-loaded cellulose fluorescent adsorption material prepared in Example 1 using steel slag as the iron source;
[0032] Figure 5 This is the FT-IR spectrum of the iron hydroxide loaded cellulose fluorescent adsorption material prepared in Example 1 using steel slag as the iron source;
[0033] Figure 6 The adsorption of different concentrations of Cr by the adsorption materials in Examples 3, 6-10 is shown in FIG. 6+ adsorption capacity;
[0034] Figure 7The carbon quantum dot solution C has different concentrations of Cr 6+ Fluorescence intensity change diagram of
[0035] Figure 8 This is the fluorescence intensity change diagram of carbon quantum dot solution C to different heavy metal ions;
[0036] Figure 9 It is the abstract figure of the present invention. Specific implementation method:
[0037] The specific implementation steps of the method of the present invention are:
[0038] (1) The milled steel slag powder is dissolved in a formic acid solution of a certain concentration to obtain a uniformly mixed steel slag mixture, which is reacted at 60°C for 4 hours. After the reaction is completed, the mixture is centrifuged to obtain leachate A.
[0039] (2) The pH of the obtained leachate A is adjusted with sodium hydroxide solution, and after stirring for a certain period of time, a reddish-brown mixed solution is obtained. After centrifugation, washing, and drying, a reddish-brown substance B is obtained.
[0040] (3) Weigh citric acid and ethylenediamine, react in deionized water for a period of time, and then place in a high-pressure reactor and react at 200°C for 5 hours; let it stand to room temperature, use a 0.22 μm membrane to filter out other impurities, and finally obtain carbon quantum dot solution C through dialysis.
[0041] (4) The adsorption material was prepared by the sol-gel method. 0.1-0.4 g of reddish-brown substance B was taken and dissolved in 20 mL of deionized water. After mixing evenly, carboxymethyl cellulose was added and reacted for 1 h. Then, polyethyleneimine solution and epichlorohydrin were added and mixed evenly and ultrasonicated. Then, the mixture was reacted in a 60°C water bath for 2-4 h to obtain an iron hydroxide-loaded cellulose adsorption material. The mixture was then washed and soaked in deionized water to remove unreacted substances. The mixture was then soaked in a carbon quantum dot solution C. After washing and freeze-drying, an iron hydroxide-loaded cellulose fluorescent adsorption material was obtained.
[0042] (5) The adsorption material synthesized in step (4) was used as an adsorbent to treat heavy metal ion wastewater. The adsorption experiment adopted a batch reaction. After the reaction was completed, the solution was filtered using a 0.22 μm filter head. The Cr in the solution after adsorption was 6+ The concentration was determined by diphenylcarbazide spectrophotometry.
[0043] The present invention will be further described below with reference to specific examples, but the present invention is not limited to the following examples.
[0044] Comparative Example 1
[0045] (1) 10 g of ball-milled steel slag powder was dissolved in 100 mL of 5% formic acid solution to obtain a uniformly mixed steel slag mixture. The mixture was reacted at 60°C for 4 h. After the reaction, the mixture was centrifuged at 6000 rpm to obtain leachate A. The iron ions in leachate A were detected and calculated, and the leaching rate of iron ions in the steel slag was 3.23%.
[0046] (2) The pH of the obtained leachate A was adjusted with 20% sodium hydroxide solution and stirred for a certain period of time to obtain a reddish-brown mixed solution. After centrifugation, washing and drying, a reddish-brown substance B was obtained. The reddish-brown substance B was subjected to XRD analysis. The results are as follows: Figure 1 As shown, it can be seen that the reddish-brown substance B is iron hydroxide.
[0047] (3) Weigh 1.5 g of citric acid and 1.26 g of ethylenediamine and react them in 10 mL of deionized water for 15 min. Then, place them in a high-pressure reactor and react at 200 °C for 5 h. Let them stand at room temperature, filter out other impurities using a 0.22 μm membrane, and finally dialyze to obtain a carbon quantum dot solution C. Figure 2 This is the FT-IR spectrum of carbon quantum dot solution C, at 1631 cm -1 and 1590cm -1 The peaks at are the stretching vibrations of -CO-NH and -NH2, which are also the characteristic peaks of carbon quantum dot solution C.
[0048] (4) The adsorption material was prepared by the sol-gel method. 0.4 g of reddish-brown substance B was taken and dissolved in 20 mL of deionized water. After magnetic stirring for 30 min, 0.75 g of carboxymethyl cellulose was added and reacted for 1 h. Then 5 mL of polyethyleneimine solution and 2 mL of epichlorohydrin were added, mixed evenly and ultrasonicated for 1 h. The mixture was then reacted in a 60 °C water bath for 4 h to obtain an iron hydroxide-loaded cellulose adsorption material. The mixture was then washed with deionized water and soaked for 48 h to remove unreacted substances. The mixture was then soaked in a carbon quantum dot solution C. After washing and freeze-drying, an iron hydroxide-loaded cellulose fluorescent adsorption material was obtained.
[0049] (5) The adsorption material synthesized in step (4) is used as an adsorbent to treat heavy metal ion wastewater. The specific treatment process is as follows: The adsorption experiment adopts an intermittent reaction. After the reaction is completed, the solution is filtered using a 0.22μm filter head. The Cr in the solution after adsorption is 6+ The concentration was determined by diphenylcarbazide spectrophotometry.
[0050] Comparative Example 2
[0051] (1) 10 g of ball-milled steel slag powder was dissolved in 100 mL of 10% formic acid solution to obtain a uniformly mixed steel slag mixture. The mixture was reacted at 60°C for 4 h. After the reaction, the mixture was centrifuged at 6000 rpm to obtain leachate A. The iron ions in leachate A were detected and calculated, and the leaching rate of iron ions in the steel slag was 34.12%.
[0052] (2) The pH of the obtained leachate A is adjusted with a 20% sodium hydroxide solution, and after stirring for a certain period of time, a reddish-brown mixed solution is obtained. After centrifugation, washing, and drying, a reddish-brown substance B is obtained.
[0053] (3) Weigh 1.5 g of citric acid and 1.26 g of ethylenediamine and react them in 10 mL of deionized water for 15 min. Then, place them in a high-pressure reactor and react at 200 °C for 5 h. Let them stand at room temperature, filter out other impurities using a 0.22 μm membrane, and finally obtain carbon quantum dot solution C through dialysis.
[0054] (4) The adsorption material was prepared by the sol-gel method. 0.4 g of reddish-brown substance B was dissolved in 20 mL of deionized water and magnetically stirred for 30 min. 0.75 g of carboxymethyl cellulose was then added and reacted for 1 h. 5 mL of polyethyleneimine solution and 2 mL of epichlorohydrin were then added, mixed evenly, and ultrasonicated for 1 h. The mixture was then reacted in a 60°C water bath for 4 h to obtain the iron hydroxide-loaded cellulose adsorption material. The mixture was then washed with deionized water and soaked for 48 h to remove unreacted substances. The mixture was then soaked in carbon quantum dot solution C. After washing and freeze-drying, the iron hydroxide-loaded cellulose fluorescent adsorption material was obtained.
[0055] (5) The adsorption material synthesized in step (4) is used as an adsorbent to treat heavy metal ion wastewater. The specific treatment process is as follows: The adsorption experiment adopts an intermittent reaction. After the reaction is completed, the solution is filtered using a 0.22μm filter head. The Cr in the solution after adsorption is 6+ The concentration was determined by diphenylcarbazide spectrophotometry.
[0056] Comparative Example 3
[0057] (1) 10 g of ball-milled steel slag powder was dissolved in 100 mL of 20% formic acid solution to obtain a uniformly mixed steel slag mixture. The mixture was reacted at 60°C for 4 h. After the reaction, the mixture was centrifuged at 6000 rpm to obtain leachate A. The iron ions in leachate A were detected, and the calculated leaching rate of iron ions in the steel slag was 53.29%.
[0058] (2) The pH of the obtained leachate A is adjusted with a 20% sodium hydroxide solution, and a reddish-brown mixed solution is obtained after stirring for a certain period of time; a reddish-brown substance B is obtained after centrifugation, washing, and drying.
[0059] (3) Weigh 1.5 g of citric acid and 1.26 g of ethylenediamine and react them in 10 mL of deionized water for 15 min. Then, place them in a high-pressure reactor and react at 200 °C for 5 h. Let them stand at room temperature, filter out other impurities using a 0.22 μm membrane, and finally obtain carbon quantum dot solution C through dialysis.
[0060] (4) The adsorption material was prepared by the sol-gel method. 0.4 g of reddish-brown substance B was dissolved in 20 mL of deionized water and magnetically stirred for 30 min. 0.75 g of carboxymethyl cellulose was added and reacted for 1 h. 5 mL of polyethyleneimine solution and 2 mL of epichlorohydrin were then added, mixed evenly, and ultrasonicated for 1 h. The mixture was then reacted in a 60°C water bath for 4 h to obtain an iron hydroxide-loaded cellulose adsorption material. The mixture was then washed with deionized water and soaked for 48 h to remove unreacted substances. The mixture was then soaked in a carbon quantum dot solution C, washed, and freeze-dried to obtain an iron hydroxide-loaded cellulose fluorescent adsorption material.
[0061] (5) The iron hydroxide loaded cellulose adsorption material synthesized in step (4) is used as an adsorbent to treat heavy metal ion wastewater. The specific treatment process is as follows: The adsorption experiment adopts an intermittent reaction. After the reaction is completed, the solution is filtered using a 0.22 μm filter head. The Cr in the solution after adsorption is 6+ The concentration was determined by diphenylcarbazide spectrophotometry.
[0062] Comparative Example 4
[0063] (1) 10 g of ball-milled steel slag powder was dissolved in 100 mL of 20% formic acid solution to obtain a uniformly mixed steel slag mixture. The mixture was reacted at 60°C for 4 h. After the reaction, the mixture was centrifuged at 6000 rpm to obtain leachate A. The iron ions in leachate A were detected, and the calculated leaching rate of iron ions in the steel slag was 53.29%.
[0064] (2) The pH of the obtained leachate A is adjusted with a 20% sodium hydroxide solution, and a reddish-brown mixed solution is obtained after stirring for a certain period of time; a reddish-brown substance B is obtained after centrifugation, washing, and drying.
[0065] (3) Weigh 1.5 g of citric acid and 1.26 g of ethylenediamine and react them in 10 mL of deionized water for 15 min. Then, place them in a high-pressure reactor and react at 200 °C for 5 h. Let them stand at room temperature, filter out other impurities using a 0.22 μm membrane, and finally obtain carbon quantum dot solution C through dialysis.
[0066] (4) The adsorption material was prepared by the sol-gel method. 0.4 g of reddish-brown substance B was taken and dissolved in 20 mL of deionized water. After magnetic stirring for 30 min, 0.75 g of carboxymethyl cellulose was added and reacted for 1 h. Then, 5 mL of polyethyleneimine solution and 2 mL of epichlorohydrin were added, mixed evenly and ultrasonicated for 1 h. Then, the mixture was reacted in a 60 °C water bath for 4 h to obtain an iron hydroxide-loaded cellulose adsorption material. The mixture was then washed with deionized water and soaked for 48 h to remove unreacted substances. The mixture was then soaked in a carbon quantum dot solution C. After washing and freeze-drying, the iron hydroxide-loaded cellulose fluorescent adsorption material was obtained.
[0067] (5) The reddish brown substance B obtained in step (2) was used as an adsorbent to treat heavy metal ion wastewater. The specific treatment process is as follows: The adsorption experiment adopts a batch reaction, the adsorbent mass is 0.05g, Cr 6+ The concentration was 50 mg / L, the volume was 50 mL, the pH was 3, the reaction temperature was 30 ° C, and the reaction time was 4 h. After the reaction, the solution was filtered using a 0.22 μm filter head. The Cr in the solution was adsorbed. 6+ The concentration was measured by diphenylcarbazide spectrophotometry, in which the Cr 6+ The standard working curve is as follows Figure 3 As shown, it is calculated that the reddish brown substance B has a strong effect on Cr 6+ The adsorption capacity is 36.74 mg / g.
[0068] Example 1
[0069] (1) 10 g of ball-milled steel slag powder was dissolved in 100 mL of 20% formic acid solution to obtain a uniformly mixed steel slag mixture, which was reacted at 60°C for 4 h. After the reaction, the mixture was centrifuged at 6000 rpm to obtain leachate A.
[0070] (2) The pH of the obtained leachate A is adjusted with a 20% sodium hydroxide solution, and a reddish-brown mixed solution is obtained after stirring for a certain period of time; a reddish-brown substance B is obtained after centrifugation, washing, and drying.
[0071] (3) Weigh 1.5 g of citric acid and 1.26 g of ethylenediamine and react them in 10 mL of deionized water for 15 min. Then, place them in a high-pressure reactor and react at 200 °C for 5 h. Let them stand at room temperature, filter out other impurities using a 0.22 μm membrane, and finally obtain carbon quantum dot solution C through dialysis.
[0072] (4) The adsorption material was prepared by the sol-gel method. 0.2 g of reddish-brown substance B was taken and dissolved in 20 mL of deionized water. After magnetic stirring for 30 min, 0.75 g of carboxymethyl cellulose was added and reacted for 1 h. Then 5 mL of polyethyleneimine solution and 2 mL of epichlorohydrin were added, mixed evenly and ultrasonicated for 1 h. Then, the mixture was reacted in a 60 ° C water bath for 4 h to obtain an iron hydroxide-loaded cellulose adsorption material. The mixture was then washed with deionized water and soaked for 48 h to remove unreacted substances. The mixture was then soaked in carbon quantum dot solution C, washed, and freeze-dried to obtain an iron hydroxide-loaded cellulose fluorescent adsorption material. Figure 4 and Figure 5 The successful loading of the reddish-brown substance B and the carbon quantum dot solution C on the carboxymethyl cellulose skeleton was demonstrated.
[0073] (5) The iron hydroxide loaded cellulose adsorption material synthesized in step (4) is used as an adsorbent to treat heavy metal ion wastewater. The specific treatment process is as follows: The adsorption experiment adopts a batch reaction, the adsorbent mass is 0.05g, Cr 6+ The concentration was 50 mg / L, the volume was 50 mL, the pH was 3, the reaction temperature was 30 ° C, and the reaction time was 4 h. After the reaction, the solution was filtered using a 0.22 μm filter head. The Cr in the solution was adsorbed. 6+ The concentration was measured by diphenylcarbazide spectrophotometry, and the adsorbent was calculated to be 6+ The adsorption capacity is 46.1 mg / g.
[0074] Example 2
[0075] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater treatment, Cr 6+ The initial concentration was 50 mg / L, and other adsorption conditions were the same as in Example 1. The variation of adsorption capacity with adsorption time was studied. The experimental results showed that the adsorption equilibrium time was 120 min and the equilibrium adsorption capacity was 46.34 mg / g.
[0076] Example 3
[0077] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater treatment, Cr 6+ The initial concentration of Cr is 50 mg / L, and the other adsorption conditions are the same as those in Example 1, except that the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 34.83 mg / g
[0078] Example 4
[0079] The iron hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater treatment, Cr 6+ The initial concentration of Cr was 50 mg / L, and the other adsorption conditions were the same as those in Example 1, except that the adsorption temperature was 45 °C and the mass of the adsorbent was 0.07 g. 6+ The adsorption capacity is 34.89 mg / g.
[0080] Example 5
[0081] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater treatment, Cr 6+ The initial concentration of Cr is 50 mg / L, and the other adsorption conditions are the same as those in Example 1, except that the adsorption temperature is 60 ° C and the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 35.6 mg / g.
[0082] Example 6
[0083] The iron hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater was treated, and other adsorption conditions were the same as in Example 1, except that Cr 6+ The initial concentration of Cr is 100 mg / L and the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 70.86 mg / g.
[0084] Example 7
[0085] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater was treated, and other adsorption conditions were the same as in Example 1, except that Cr 6+ The initial concentration of Cr is 150 mg / L and the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 101.46 mg / g.
[0086] Example 8
[0087] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater was treated, and other adsorption conditions were the same as in Example 1, except that Cr 6+ The initial concentration of Cr is 200 mg / L, and the mass of the adsorbent is 0.07 g. 6+The adsorption capacity is 119.54 mg / g.
[0088] Example 9
[0089] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater was treated, and other adsorption conditions were the same as in Example 1, except that Cr 6+ The initial concentration of Cr is 300 mg / L and the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 147.68 mg / g.
[0090] Example 10
[0091] The ferric hydroxide loaded cellulose fluorescent adsorption material synthesized in Example 1 with steel slag as the iron source was used as the adsorbent to 6+ Wastewater was treated, and other adsorption conditions were the same as in Example 1, except that Cr 6+ The initial concentration of Cr is 400 mg / L and the mass of the adsorbent is 0.07 g. 6+ The adsorption capacity is 151.3 mg / g.
[0092] The ferric hydroxide loaded cellulose fluorescent adsorption material with steel slag as the iron source in Examples 3, 6-10 has a significant effect on the Cr 6+ Adsorption capacity comparison Figure 6 As the initial Cr 6+ With the increase of concentration, the adsorption capacity of the adsorbent for Cr6+ increases accordingly, and it basically reaches saturation when the initial concentration is 400 mg / L, and the maximum adsorption capacity at this time is 151.3 mg / g.
[0093] Example 11
[0094] The carbon quantum dot solution C synthesized in Example 1 was used to study its effect on Cr 6+ Fluorescence detection, configured with Cr concentrations ranging from 0-100 mg / L 6+ Solution, take 10mL, add 0.5mL of carbon quantum dot solution C, and then measure its fluorescence intensity. The results are as follows Figure 7 As shown, it can be seen that as Cr 6+ With the increase of concentration, the fluorescence intensity of carbon quantum dot solution C decreases. This is because Cr 6 + The presence of carbon quantum dot solution C leads to fluorescence quenching, which also shows that carbon quantum dot solution C has a strong effect on Cr 6+ The fluorescence responsiveness and sensitivity are strong, proving that it can be applied to Cr in solution. 6+ Detection.
[0095] Example 12
[0096] The selectivity of carbon quantum dots to heavy metal ions was studied using the carbon quantum dot solution C synthesized in Example 1. The Ca 2+ , Fe 3+ , Pb 2+ , Cd 2+ and Cr 6+ Solution, take 10mL, add 0.1mL of carbon quantum dot solution C, and then measure its fluorescence intensity. The results are as follows Figure 8 As shown, the carbon quantum dot solution C in Cr 6+ The solution will produce a significant fluorescence quenching effect, while the effect on other heavy metal ions is small, indicating that the carbon quantum dot solution C has a significant effect on Cr 6+ The high selectivity and sensitivity of Cr 6+ Stronger electron capture ability will lead to strong fluorescence quenching of carbon quantum dot solution C, ultimately achieving the effect of Cr 6+ Purpose of testing.
Claims
1. A Cr 6+ The preparation method of the iron hydroxide loaded cellulose fluorescent adsorption material with steel slag as the iron source is characterized in that: The following steps are involved: (1) Dissolve steel slag powder in a container A filled with an acid solution of a certain concentration to obtain a uniformly mixed steel slag mixture, heat and stir to obtain a steel slag mixture containing calcium and iron ions, and then centrifuge to obtain leachate A and leach slag A. (2) The pH of the obtained leachate A is regulated by using an alkaline solution of a certain concentration, and a reddish-brown mixed solution is obtained after stirring for a certain period of time. The reddish-brown mixed solution is centrifuged, washed, and dried to obtain a reddish-brown substance B, which is ferric hydroxide. (3) At least one selected from lignin, cellulose and citric acid as a carbon source and at least one selected from dopamine, o-phenylenediamine and ethylenediamine as a nitrogen source are placed in a sealed container B for reaction, and a carbon quantum dot solution C is obtained after dialysis. (4) Mixing the reddish-brown substance B, a polymer having an amino group, at least one selected from glutaraldehyde and epichlorohydrin as a cross-linking agent, and a cellulose-based substance having hydroxyl groups and carboxyl groups in water, performing ultrasonication and reaction, and then washing the mixture. The mixture is then immersed in a carbon quantum dot solution C. After washing and freeze-drying, the iron hydroxide-loaded cellulose fluorescent adsorption material with steel slag as the iron source is obtained.
2. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (1), the concentration of steel slag powder in the steel slag mixture is 70-170 g / L; the container A is a conventional glass container, the acid concentration of the acid solution is 5wt%-40wt%; the stirring speed is 200-500 rpm, the heating temperature is 25-70°C; and the stirring time is 1-6h.
3. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (1), the acid component in the acid solution is hydrochloric acid, acetic acid, nitric acid or formic acid.
4. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (2), the alkali concentration in the alkali solution is 10wt%-30wt%, the stirring speed is 200-500rpm; the centrifugal speed is 5000-6000rpm, the washing times are 2-4 times, and the drying time is 12-48h.
5. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (2), the alkali component in the alkali solution is sodium hydroxide or potassium hydroxide.
6. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (3), the sealed container B is a hydrothermal reactor or a high-pressure reactor; and the dialysis time is 1-2 days.
7. The method for preparing a cellulose fluorescent adsorption material loaded with iron hydroxide using steel slag as an iron source according to claim 1, characterized in that: In step (4), the polymer having an amino group is selected from polyacrylamide and polyethyleneimine, and is uniformly mixed with the reddish-brown substance B and the cellulose substance in step (2); and 1-4 mL of the cross-linking agent having a cross-linking effect is added; the ultrasonic time is 40-60 min, the reaction temperature is 50-70° C., the reaction time is 2-4 h, the soaking time is 24-48 h, and the number of washing times is 2-4 times.
8. The method for preparing the iron hydroxide-loaded cellulose fluorescent adsorption material using steel slag as the iron source according to claim 1, characterized in that: In step (4), the cellulose material is cellulose or carboxymethyl cellulose.
9. A ferric hydroxide-loaded carboxymethyl cellulose fluorescent adsorption material using steel slag as an iron source, characterized in that: The invention can be prepared by the preparation method according to any one of claims 1 to 8.
10. A cellulose fluorescent adsorption material loaded with iron hydroxide using steel slag as the iron source for the adsorption and detection of Cr 6+ Purpose.
Citation Information
Patent Citations
Method of preparing high-purity light calcium carbonate with steel slag
CN104828850A